Who are Feminists and what do they Believe? The Role of Generations - Schnittker, Jason; Freese, Jeremy; Powell, Brian (American Sociological Review, 2003)
Using the 1996 General Social Survey, the antecedents of feminist self-identification and their link to gender-related social attitudes are explored. Although most sociodemographic variables show either no relationship or a weak relationship with feminist self-identification, there are strong differences across cohorts. Males and females who were young adults during the “second wave “ of feminism (birth years 1936 to 1955) are more likely to identify as feminists than are those younger or older. In addition, the link between feminist self-identification and some social attitudes is cohort specific: Seemingly profeminist positions distinguish self-identified feminists from nonfeminists only among members of the “second-wave” generation. These results reinforce the importance of political generation and suggest increasing heterogeneity in public conceptions of feminism.